To analyze the recursive definition given for the sequence:
- Base case: \( a_1 = 6 \)
- Recursive case: \( a_n = a_{n-1} + 2 \)
We can calculate the first few terms of the sequence:
- \( a_1 = 6 \)
- \( a_2 = a_1 + 2 = 6 + 2 = 8 \)
- \( a_3 = a_2 + 2 = 8 + 2 = 10 \)
- \( a_4 = a_3 + 2 = 10 + 2 = 12 \)
- \( a_5 = a_4 + 2 = 12 + 2 = 14 \)
From this calculation, we can see that the sequence is: \( 6, 8, 10, 12, 14, \ldots \)
This represents an arithmetic sequence where the first term is 6 and the common difference is 2. The general formula for the \( n^{th} \) term of an arithmetic sequence is:
\[ a_n = a_1 + (n - 1) \cdot d \]
Where \( d \) is the common difference. In this case:
- \( a_1 = 6 \)
- \( d = 2 \)
So the formula becomes:
\[ a_n = 6 + (n - 1) \cdot 2 = 6 + 2n - 2 = 2n + 4 \]
This formula does not match the provided choices directly. However, analyzing the response options, we note that:
- \( a_n = 8, 10, 12, 14, 16, \ldots \) matches our calculated sequence, starting at 8.
Therefore, the correct option based on the recursive definition is:
Response:
- \( a_n = 8, 10, 12, 14, 16, \ldots \)